Catalytic Asymmetric Synthesis of α-Mono and α,α-Disubstituted 5- and 6-Membered α-Aza-lactams - Palomo, Claudio; Landa, Aitor; Oiarbide, Mikel (Synthesis, 2024)
Five- and six-membered cyclic amide structures with an embedded endocyclic α-aza group (α-aza-lactams) not only represent masked or protected forms of α-amino acids, but also form the core of other medicinally relevant compound families such as (thio)hydantoins and di(tri)ketopiperazines. In recent years, catalytic methods have been discovered to synthesize these molecular scaffolds, particularly those bearing an α-stereogenic tri- or tetrasubstituted carbon center, enantioselectively. The wide variety of methods and catalytic activation strategies that have been successfully applied to this end in a short period of years is notable. This short review covers the most significant, highlighting their differences and complementarities. The methods are organized according to the disconnection approach to the target α-aza-lactam structure, which in most cases is deeply bound to the type of catalysis applied.1 Introduction2 Catalyst-Controlled Cα–H Functionalization (Approach a)3 Decarboxylative α-AAA Reactions (Approach b)4 Cα–X Substitution Reactions (Approach c)5 De Novo Synthesis from Acyclic Precursors (Approach d)6 Hydrogenation of (Addition to) α-Alkyliden-α-aza-lactams (Approach e)7 Kinetic Resolution and Deracemization (Approach f)8 Conclusions
Keywords: asymmetric catalysis; α-aza-lactams; hydantoins; diketopiperazines; α-amino acids; quaternary centers